Islamic Boarding School Education Model (IB-SEM) to Create Leadership Integrity: Using NVivo 12 Analysis - Diding Nurdin; Suparta Rasyid (STAI Hubbulwathan Duri, 2022)
The purpose of this research is to create the character of a leader with integrity. Many problems are related to the honesty of the leader. This research method uses qualitative Design-Based Research (DBR), the qualitative data obtained is then processed using the NVivo 12 Plus application. The participants consisted of twenty-one participants, who came from two different Islamic boarding schools. The participants’ character consists of the principal, vice principal, kyai, mudaris, musyrif, and Islamic students. The results of the study show that there is a very strong impact on the formation of leader character and integrity through coaching in Islamic boarding schools. Educational guidance is carried out through 24-hour supervision every day while the students are in boarding school. The conclusion is that based on the results of the study, the coaching carried out at this Islamic boarding school must be a model for fostering Islamic students or students in Indonesia, especially students in Islamic boarding schools. integrated Islamic boarding school environment.